Clinical significance and influencing factors of fibrinogen in ANCA-associated vasculitis: A single-center retrospective study from Southwest China. Issue 39 (25th September 2020) - Zhang, Naidan; Sun, Jiaxiang; Ji, Chaixia; Zhou, Yusha; Bao, Xiao; Yuan, Chengliang
Abstract : Abstract: Hypercoagulable is an important pathological state in anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV). Fibrinogen (FIB) is the main protein in coagulation process. In this study, we aimed to investigate the clinical significance and influencing factors of FIB in AAV from Southwest China. A retrospective study was performed on AAV patients from Peoples Hospital of Deyang City from January 2007 to December 2018. Demographic and clinical characteristics were collected. A total of 463 AAV patients were included. In Wilcoxon rank sum test, FIB was significantly higher in AAV active group than inactive group ( P  = .005). FIB was also higher in bacterial infection group than in non-infection group both in active group ( P  = .008) and inactive group ( P  = .017). In receiver operating characteristic (ROC) curve analysis, the critical value of FIB for diagnosis of bacterial infection between AAV active and inactive groups was 3.385 g/L ( P  = .030), with sensitivity of 70.2% and specificity of 52.9%. In the multivariate analysis of variance (MANOVA), estimated glomerular filtration rate (eGFR) was shown to be an independent factor for FIB ( P  = .001). Least-significant difference showed the concentration of FIB ( P  < .05) increased with renal impairment, especially in endstage kidney disease (ESKD). FIB identified a certain reference value in distinguishing AAV activity from bacterial infection. ESKD had a statistical effect on it. Influencing factors of FIB should be evaluated based on the renal function impairment of patients. Abstract : Supplemental Digital Content is available in the text